Qualidade de vida urbana no município de Belo Horizonte: análise de confronto entre informações subjetivas e indicadores quantitativos - Natalia Cunha Fahel (2015)
The quality of urban life is a key issue to be considered to meet the needs and expectations of local people and attract investments to urban centers. Many statistical models for analyzing the quality of urban life have been developed. Nevertheless, in most cases, these models focus only on quantitative indicators. Therefore, relevant aspects in relation to the opinion of the population, within the urban context, are not considered. In this work, a model of Logistic Regression Ordered Multilevel is developed for analyzing the quality of urban life in the city of Belo Horizonte, based on a recent survey data held in this city with subjective information of the population. The results of this research about satisfaction levels of the public opinion regarding access and availability of services are faced, using the proposed model, with quantitative data such as the Quality of Life Index of service sectors. It is concluded that the level of satisfaction with access to health centers and level of noise conditions due to bars or neighbors and businesses doesnt reflect the Quality of Life Index in the healthcare and environment sectors respectively. When comparing the coefficient of IQVU with a standard error, it is observed that there is bigger significant in the association between the declared satisfaction levels and the IQVU of corresponding service sector in the following cases: quality air conditions, access to hospitals, supermarkets, private schools of high school and elementary school, availability of street paving, public transportation and telephone service. In this analysis it was considered a strong significance when P <0.001. Others IQVU are less significant in the association between the declared satisfaction levels and the IQVU of corresponding service sector in the following cases: conditions of green areas, crime, violence, vandalism, traffic safety and noise due to traffic, access the public schools and availability of electricity.